ANALISIS USAHA AGROINDUSTRI TAHU (Studi Kasus pada Usaha Agroindustri Tahu Bapak Warnok di Desa Kuok Kecamatan Kuok Kabupaten Kampar) - Ade ' Saputra; Evy ' Maharani; Didi ' Muwardi (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2016)
This research is aimed to know the total costs, income, efficiencyand the added value of tofu agroindustry. This research was conducted on March until April 2016. Then, This research used case-study method. From a research had been conductedto Agroindustry, it can be summarized that: (1) The Total costs incurred by businessman is Rp. 40.275.252 per month. The acceptance obtained by businessman is Rp. 71.200.000 per month. The Benefits obtained by them is of Rp 30.924.747,96 per month. (2) It can be concluded that the Tofu business gets the RCR value >1,00that is1.77. It means that each Rp1,00 incurred will provide gross revenues as much as Rp1,77 and a net income as much as Rp.77. This shows that the business is lucrative/ beneficialto be continued. RCR is obtained from gross income divided by the total cost of production. For BEP analysis, it can be seen that the Tofu agroindustry business get capital turning point at the cost of Rp1.214.474,3 with total production as much as 3.279,08 sliced tofu. This means that at the time of this condition, the running business does not get benefits but also do not experience loss (balance). (3) added value obtained from the business is Rp 8.184,04 /kg. While the ratio of the addedvalue known is 51,15 percent, this means that every Rp100,00 from the output value consistof Rp51,15 of the added value. Key Words: Agroindustry tofu, added value, cost, production.